1984
DOI: 10.3382/ps.0631262
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Amelioration of Steroid-Mediated Immunosuppression by Ascorbic Acid

Abstract: Four experiments were conducted to determine if supplemental ascorbic acid (AA) would ameliorate the immunosuppression induced by exogenous cortisol (COL). Supplemental AA was provided in the diets at levels of 0 and 1000 ppm. Administration of COL significantly lowered plasma AA at both 0 and 10 days postimmunization, and AA supplementation elevated plasma AA at both times. Cortisol-treated chicks exhibited significantly reduced agglutinins to sheep red blood cells but not to Brucella abortus. Supplemental AA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
1
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(17 citation statements)
references
References 29 publications
2
13
1
1
Order By: Relevance
“…Although poultry are able to synthesize vitamin C and they do not need an exogenous source of vitamin C, it has been documented that particular environmental stressors can alter ascorbic acid utilization or synthesis in avian species (Pardue and Thaxton, 1984). It has been also reported that ascorbic acid synthesis is inadequate under stress conditions such as low or high environmental temperatures, humidity, high productive rate, and parasite infestation (McDowell, 1989;Cheng et al, 1990).…”
Section: Introductionmentioning
confidence: 98%
“…Although poultry are able to synthesize vitamin C and they do not need an exogenous source of vitamin C, it has been documented that particular environmental stressors can alter ascorbic acid utilization or synthesis in avian species (Pardue and Thaxton, 1984). It has been also reported that ascorbic acid synthesis is inadequate under stress conditions such as low or high environmental temperatures, humidity, high productive rate, and parasite infestation (McDowell, 1989;Cheng et al, 1990).…”
Section: Introductionmentioning
confidence: 98%
“…Corticosterone concentration in the heat and no AA treatment was found to be significantly higher than in the other three treatments if the level of significance was tested at the .10 level of probability. Pardue and Thaxton (1984) reported that AA ameliorated the immune suppression in broiler chicks. However, these authors used only two dietary levels of AA (0 and 1000 ppm) and exogenous cortisol injections.…”
Section: Corticosterone Assaymentioning
confidence: 99%
“…Vitamin C supplementation was expected to decrease corticosterone concentration as vitamin C inhibits glucocorticoid synthesis (Pardue et al, 1985). Vitamin C is also known to increase the use of corticosteroids released during stress (Pardue and Thaxton, 1984), thus playing an important role in responding to stress. Vitamin C and chromium have been shown to alleviate the negative eects of stress such as cold stress-related depression in poultry performance (McDowell, 1989; Sahin et al, 2001a).…”
Section: Discussionmentioning
confidence: 99%